2007
DOI: 10.1093/bja/ael277
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sevoflurane and propofol on left ventricular diastolic function in patients with pre-existing diastolic dysfunction

Abstract: During spontaneous breathing, early diastolic function improved in the sevoflurane but not in the propofol group. However, during positive pressure ventilation and balanced anaesthesia, there was no evidence of different effects caused by the two anaesthetics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
31
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 31 publications
4
31
0
2
Order By: Relevance
“…The physiologic effects of general anaesthesia and positive pressure ventilation on LV cavity size were recently demonstrated in a magnetic resonance imaging study in healthy adults (10) and several echocardiographic studies in healthy subjects and in patients with cardiac disease (9,(31)(32)(33). All these studies reported that LV cavity dimensions were reduced during anaesthesia and positive pressure ventilation, most likely as a consequence of decreased venous return and LV preload.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The physiologic effects of general anaesthesia and positive pressure ventilation on LV cavity size were recently demonstrated in a magnetic resonance imaging study in healthy adults (10) and several echocardiographic studies in healthy subjects and in patients with cardiac disease (9,(31)(32)(33). All these studies reported that LV cavity dimensions were reduced during anaesthesia and positive pressure ventilation, most likely as a consequence of decreased venous return and LV preload.…”
Section: Discussionmentioning
confidence: 89%
“…However, such values might not necessarily apply for patients with coronary heart disease. Further, even if normative values obtained using transoesophageal echocardiography (TOE) in awake subjects are applied (6,7), anaesthetic drugs, positive pressure ventilation and patient positioning may have systematic effects on cardiac function and loading conditions causing small, but important differences in LV EDA and EDD measurements in the anaesthetised and ventilated patients (8)(9)(10). Finally, TTE values might be different from those for TOE as a consequence of small differences in the position of the echo probe and the slightly different standard echocardiographic cross-sectional views used in the two techniques (11).…”
Section: Introductionmentioning
confidence: 99%
“…Anesthesia was maintained with sevoflurane in the majority of the patients (84%), whereas anesthesia was maintained with propofol in the remaining patients. Filipovic et al [25] reported no differences in E m , A m , or S m between the sevoflurane and propofol groups with intermittent positive pressure ventilation. On this basis, we consider that the choice of the anesthetic agents in our study did not affect the TDI variables.…”
Section: Discussionmentioning
confidence: 96%
“…In animal studies [32,33], propofol has not been found to affect diastolic function. Filipovic et al [34] randomised 20 patients to sevoflurane and 20 to propofol undergoing minor surgery. Echocardiography was performed pre-operatively, during induction of anaesthesia and following mechanical ventilation of the lungs.…”
Section: Discussionmentioning
confidence: 99%